(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
When dialoguing with legal frameworks related to University Extension, we chose to reflect on some extension actions that problematize the challenges imposed by the curricularization of extension in Theater Degree courses, paying attention to CNE/CP Resolution No. 4, of May 29, 2024. It is concluded that such a resolution, by restricting the execution of curricular extension actions to Basic Education institutions, highlights a paradox: it expands the horizons of theater practices at school, but tends limiting the training experiences of people with a degree in theater, prevented from developing curricular extension actions in non-formal education.